The Moral Self-Image Scale: Measuring and Understanding the Malleability of the Moral Self - Jordan, Jennifer; Leliveld, Marijke C.; Tenbrunsel, Ann E. (Frontiers in Psychology, 2015)
Recent ethical decision-making models suggest that individuals’ own view of their morality is malleable rather than static, responding to their (im)moral actions and reflections about the world around them. Yet no construct currently exists to represent the malleable state of a person’s moral self-image (MSI). In this investigation, we define this construct, as well as develop a scale to measure it. Across five studies, we show that feedback about the moral self alters an individual’s MSI as measured by our scale. We also find that MSI is related to, but distinct from, related constructs, including moral identity, self-esteem, and moral disengagement. In Study 1, we administered the MSI scale and several other relevant scales to demonstrate convergent and discriminant validity. In Study 2, we examine the relationship between the MSI and one’s ought versus ideal self. In Studies 3 and 4, we find that one’s MSI is affected in the predicted directions by manipulated feedback about the moral self, including feedback related to social comparisons of moral behavior (Study 3) and feedback relative to one’s own moral ideal (Study 4). Lastly, Study 5 provides evidence that the recall of one’s moral or immoral behavior alters people’s MSI in the predicted directions. Taken together, these studies suggest that the MSI is malleable and responds to individuals’ moral and immoral actions in the outside world. As such, the MSI is an important variable to consider in the study of moral and immoral behavior.